Efecto de fertilización Npk y enmiendas con Ca + Mg en el cultivo de marigold (tagetes erecta L.), en suelos ácidos de San Martín - Pezo Ruiz, César Ángel (2004)
The present research work was carried out in tropical crops Institute experimental plot (ICT) sector 'Laguna Venice' of the province and Department of San Martin in order to determine the effect of dosage of NPK fertilization and amendments of Ca + Mg (magnecal) most appropriate to get the highest yield in the culture of marigold (tagetes erecta l.) under conditions of very acidic soil. PH of 4.3 to 5.0, low, sandy loam texture soil: organic matter, nitrogen and phosphorus, with a high content of potassium and zero of limestone. The experimental design used was the "Complete blocks at random" with seven treatments and four replications. Nitrogen levels were 0.89, 178 and 336 kg of N/ha, using as source nitrogen Urea (46%); phosphorus levels were used 0,49,98, and 196 Kg/ha using as a source triple superphosphate (46%); potassium levels were 0.1 00,200 and 400 Kg/ha using as a source I chloride of potassium (60%), with respect to the magnecal used a single level of 1.5 Mt/HA. The cultivation of the marigold was established in two phases: seedling and final field; in seedbed hard 29 days and final field in 96 days, fulfilling its cycle in 125 days. Morphological aspects of the plant, was assessed during the entire crop yield and the economic analysis of each treatment. Higher total yield of flower got it treatment 4 with 8 Kg/he 470,90 and the lowest treatment 1 got it {witness) with 4 830,69 Kg/ha.} Tto 2 with 0.92 had less relationship benefit cost. The net value of production was positive in all the other treatments with income in favor that ranged from 25.53 to 308,37 new soles.